Environmental risk assessment of heavy metals contamination in the catchment of small-scale mining enclave in Prestea Huni-Valley District, Ghana. Issue 1 (31st December 2022) - Wiafe, Samuel; Awuah Yeboah, Eric; Boakye, Ebenezer; Ofosu, Samuel
ABSTRACT: The activities of illegal mining have caused devastating effect to the environment, particularly, water and soil. There is therefore the need to ascertain the extent of pollution these activities have caused both soil and water bodies. To this end, this study seeks to identify the prevalence of heavy metal contamination in soil and surface water, determine the correlation between the dominant heavy metals and to ascertain the ecological risk of pollutants in both the waterbody and the soil. The levels of nine predominant heavy metals within Prestea-Huni Valley District of artisanal mining sites were determined using Atomic Absorption Spectrometer (AAS). The extent of pollution within the soil and surface water was determined using Enrichment Factor (EF), Geoaccumulation Index (Igeo), Pollution Index (PI) and Contamination Factor (CF). The concentration of metals in water were below WHO permissible limits, except Ni and Co. The mean concentration of Hg and Cd in the soils of the study area were 2.02 mg/kg and 13.2 mg/kg respectively, which exceeded the WHO permissible limits. The study revealed that the soil and water samples were polluted with heavy metals, particularly Hg and Cd. It is recommended that the polluted sites should be remediated using eco-friendly approach. In addition, Artisanal Mining activities need to be properly regulated to protect both water and soil from further pollution.